Anthropometric, Food Intake and Consumption of Nutritional Supplements of Athletes and Competitors of Mixed Martial Arts (MMA) of Araraquara - Assis, Lilian Maria de; Silveira, Jacqueline Queiroz da [UNESP]; Barbosa, Marina Rodrigues (Inst Brasileiro Pesquisa & Ensino Fisiologia Exercicio-ibpefex, 2016)
Introduction: The MMA is a new sport category contestants compete in their categories whose weight limit is far below its actual weight. The cycle win-lose weight is repeated many times during the life of competitive athletes, and is related to some health problems, such as dysfunction of the cardiovascular system or even temporary cessation of growth. Aim: The aim of this study was investigated anthropometric profile, food and dietary supplements intake of the MMA competitors and practitioners during training. Materials and Methods: 11 male athletes in the training phase were performed anthropometric analysis of total body mass, height and skinfold. Food intake was measured by of the three 24 hour register. The intake of dietary supplements was measured by standardized questionnaire. Results: The mean age of the volunteers was 27.7 +/- 4.4 years old. Regarding anthropometric assessment were classified as overweight according to BMI (25.3 +/- 3.0 kg/m(2)). In relation to percentage of fat mass were excellent (10.8 +/- 4.2%). The macronutrients intake was inappropriate, reduced in 21.8% of carbohydrates and 16% of lipids. In relation protein intake there was twice of a higher. Conclusion: Inadequate intake of macronutrients and micronutrients can lead to reduced physical performance and increase the risk of developing nutritional diseases. More studies are needed to correlate the physical performance and food intake in order to verify the effects of food inadequacy in the performance and health of MMA athletes.
Keywords: Fight; Anthropometry; Food Intake; Ergogenic Effects